UPPAAL model for validation of the software development process - Atirah Shahira, Mahadi (2019)
Software development is a process of creating useful programs and systems to improve the quality of life. There are Software Development Life Cycles such as Waterfall, and Rapid Application Development among many others. In order to validate the process of software development it is important to use formal methods. Proving properties whether it is operational or quality ones is crucial to avoid errors and possible accidents that can cost human lives. UPPAAL timed automata was selected for development of the model of a software development process in this research. A case study was taken from a small software development company in Malaysia, corresponding model was developed and analysed, and next validated by UPPAAL. This study is beneficial for software development companies to refer and form understanding on the importance of using formal tools, allowing proving and validating the business process before the development of a software system starts.